Public morality and the Petrine ministry a Protestant perspective on a renewed moral papacy - Bruyns, Clint le (2003)
This article will attempt to build a case for Protestants to accept the Petrine office as a Petrine service of moral leadership that may potentially benefit all churches, albeit not in its present form.